Jaine Austen : Death of a Bachelorette - Book 15 - Levine, Laura, 1943- (New York, NY : Kensington Books, 2017)
"Jaines life has been a royal pain since she started penning dialogue for Some Day My Prince Will Come--a cheesy dating show that features bachelorettes competing for the heart of Spencer Dalworth VII, a very distant heir to the British throne. As if fending off golf ball-sized bugs on a sweltering island wasnt tough enough, Jaine must test her patience against an irritable production crew and fierce contestants who will do anything to get their prince. But Jaine never expected murder to enter the script. When one of the finalists dies in a freak accident, its clear someone wanted the woman out of the race for good"--Amazon.com.
Keywords: Austen, Jaine -- (Fictitious character) -- Fiction; Women authors -- Fiction; Reality television programs -- Fiction; Murder -- Investigation; Fiction; Cozy mystery fiction